Nurses’ educational practices in Family Health Strategy - Ferreira, Darlisom Sousa; Ramos, Flavia Regina Souza; Teixeira, Elizabeth (Revista Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to analyze the nurse’s educational practice in Family Health Strategy. Methods: descriptive study with a qualitative approach, whose data production used the World Café group technique, in two meetings, with 26 nurses of a health district of Manaus-AM. The technique used was Categorial-Thematic Content Analysis. Results: the study generated two units of analysis: Political and Organizational Configuration of Educational Work at ESF and Operational Configuration of Educational Work at ESF, revealing the necessary (re)configurations in co-management, in the centrality of the subject for the planning of educational work, and in (re)pactuation between the management of services and training institutions to overcome contradictions in the implementation of National Policies on Permanent Education and Basic Health Care. Conclusions: the configuration of nurses’ educational practice at ESF works toward interactions, organized to respond to health policies, incorporating creativity in doing, but facing numerous obstacles. RESUMEN Objetivos: analizar la praxis educativa de enfermeros en la Estrategia de Salud Familiar. Métodos: estudio descriptivo con abordaje cualitativo, para los datos utilizó la técnica grupal World Café, en dos encuentros, con 26 enfermeros de un distrito de salud de Manaus-AM. Se utilizó la técnica de Análisis de Contenido Categorial Temático. Resultados: han generadas dos unidades de análisis: Configuración Política y Organizacional del Trabajo Educativo y Configuración Operativa del Trabajo Educativo, en la ESF, desvelando necesarias (re)configuraciones de cogestión, centralización del sujeto para planeamiento del trabajo educativo y (re)pactuación entre la gestión de servicios y las instituciones formadoras para superación de las contradicciones en la implementación de Políticas Nacionales de Educación Permanente y Atención Básica en Salud. Conclusiones: la praxis educativa de los enfermeros en la ESF se configura en interacciones, se organiza para responder a las políticas de salud, incorporando la creatividad en el hacer, pero enfrentando innumerables obstáculos. RESUMO Objetivos: analisar a práxis educativa de enfermeiros na Estratégia Saúde da Família. Métodos: estudo descritivo com abordagem qualitativa, cuja produção dos dados utilizou a técnica grupal World Café, em dois encontros, com 26 enfermeiros de um distrito de saúde do município de ManausAM. Utilizou-se a técnica de Análise de Conteúdo Categorial-Temática. Resultados: foram geradas duas unidades de análise: Configuração Política e Organizacional do Trabalho Educativo na ESF e Configuração Operativa do Trabalho Educativo na ESF, desvelando necessárias (re)configurações na cogestão, na centralidade do sujeito para o planejamento do trabalho educativo e na (re)pactuação entre a gestão dos serviços e as instituições formadoras para superação das contradições na implementação das Políticas Nacionais de Educação Permanente e de Atenção Básica em Saúde. Conclusões: a práxis educativa dos enfermeiros na ESF se configura em interações, se organiza para responder às políticas de saúde, incorporando a criatividade no fazer, mas enfrentando inúmeros obstáculos.